The cost of living in China: Implications for inequality and poverty - Ingvild Almås; Åshild Auglænd Johnsen (University of Oslo, Department of Economics, 2013)
China's economic development in recent decades has been tremendous, but subject to debate. This paper calculates regional prices that make incomes comparable across both time and space using the Engel-curve approach. Incomes are adjusted using these price indices, providing new estimates of inequality and poverty development. Our findings contrast with measures based on the official consumer price indices (CPIs) - in a time characterized by high economic growth, we find a larger increase in inequality and a more moderate poverty reduction than what is indicated by the CPI-adjusted measures.
Keywords: D1; E31; F01; 330; Mikroökonomische Konsumfunktion; Verbraucherpreisindex; Verbraucherpreisindex; Soziale Ungleichheit; Armut; China